Zagonki jako forma pomocy mieszkańcom Łodzi w czasie I wojny światowej - Stawiszyńska, Aneta (Acta Universitatis Lodziensis. Folia Historica, 2013)
One of the biggest problems that Łódź must have coped with during the First World War was the provisional problems and the increased level of hunger among citizens. At the beginning of 1915, the concept of separating small fields that were leased to the poor inhabitants afterwards was formulated. A forementioned fields were mainly used to cultivate potatoes, but carrots, broad beans and peas were also widespread. In later years, the interest in such fields was gradually increasing. The action turned out to be successful, even concerning the educational aspect, because people taking advantage of this type of aid did not receive anything for free and must have worked to gain beneficial resources.